2023
DOI: 10.12998/wjcc.v11.i4.809
|View full text |Cite
|
Sign up to set email alerts
|

Transdiagnostic considerations of mental health for the post-COVID era: Lessons from the first surge of the pandemic

Abstract: BACKGROUND The Coronavirus disease 19 (COVID-19)-related psychiatric burden partly results from prolonged social stress world-wide. Studies have examined the psychiatric impact of COVID-19 on Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM 5) and International Classification of Diseases 11 th Revision (ICD-11) categories, implicating multiple diagnoses, complicating clinical management. AIM To verify whether COVID-19-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Furthermore, earlier studies reported that at-risk populations do not necessarily meet the full criteria of affective disorders and stress reactivity categories[ 40 , 44 ]. As it arises from the current findings, and according to our previous arguments[ 26 ], the CSRS, Type A identifies, and is sensitive to individual differences in stress reactivity and reduced positive affectivity, within a transdiagnostic spectrum.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Furthermore, earlier studies reported that at-risk populations do not necessarily meet the full criteria of affective disorders and stress reactivity categories[ 40 , 44 ]. As it arises from the current findings, and according to our previous arguments[ 26 ], the CSRS, Type A identifies, and is sensitive to individual differences in stress reactivity and reduced positive affectivity, within a transdiagnostic spectrum.…”
Section: Discussionsupporting
confidence: 75%
“…Thus, the CSRS, Type A represents a unique transdiagnostic clinical picture combining symptomatology of affective disorders with stress reactivity[ 16 , 26 , 31 ]. The prevalence of affective disorders spans a wide range of symptomatology, with dramatic cross-cultural differences[ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations